2015
DOI: 10.1097/jto.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Early Prediction of Response to Tyrosine Kinase Inhibitors by Quantification of EGFR Mutations in Plasma of NSCLC Patients

Abstract: Quantification of EGFR mutations from plasma with a standardized PCR test is feasible. To our knowledge, this is the first study showing a strong correlation between the EGFR SQI in the first days of treatment and clinical response with relevant implications for patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
123
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 16 publications
15
123
0
Order By: Relevance
“…Patients with M1a disease had lower EGFR T790M detection compared to patients with M1b disease suggesting extra-thoracic metastasis is more predictive of ctDNA detection. Our study is the first significant attempt to our knowledge to describe the kinetic rise in the number of copies of ctDNA immediately after therapy, and our findings are consistent with previously reported studies in plasma demonstrating an overall decrease in ctDNA levels for patients responding to targeted therapy with samples collected weeks to months after initiation of therapy (13, 29-30). Studies are ongoing to further understand the impact of biological factors including urine volume and residency time, timing of collection, locus dependent pattern of ctDNA degradation, and patients’ hydration status on the dynamics and detection of ctDNA in urine.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with M1a disease had lower EGFR T790M detection compared to patients with M1b disease suggesting extra-thoracic metastasis is more predictive of ctDNA detection. Our study is the first significant attempt to our knowledge to describe the kinetic rise in the number of copies of ctDNA immediately after therapy, and our findings are consistent with previously reported studies in plasma demonstrating an overall decrease in ctDNA levels for patients responding to targeted therapy with samples collected weeks to months after initiation of therapy (13, 29-30). Studies are ongoing to further understand the impact of biological factors including urine volume and residency time, timing of collection, locus dependent pattern of ctDNA degradation, and patients’ hydration status on the dynamics and detection of ctDNA in urine.…”
Section: Discussionsupporting
confidence: 90%
“…Most recently, Marchetti et al performed PCR and ultra-deep NGS on serial plasma samples of advanced-stage patients (n 5 20) with known tissue and plasma EGFR mutations before TKI treatment. Patients who had a 50% decrease in plasma EGFR copy number at 14 days (rapid responders; n 5 14) had a greater mean percentage of tumor shrinkage than that of slow responders (n 5 6) who had not achieved this change (70% vs. 30%; p , .0001) [27]. Finally, using a deep sequencing method (cancer personalized profiling by deep sequencing) that quantifies cancer-specific genomic alterations, Newman et al was able to demonstrate that plasma ctDNA levels isolated from longitudinal samples in advanced-stage patients (n 5 3) receiving either chemotherapy or targeted therapy highly correlated with the tumor volumes during therapy [28].…”
Section: Predictive and Prognostic Utility Of Egfr Mutations Identifimentioning
confidence: 97%
“…This methodology is also relevant when patients show no tolerance to a new biopsy, if there are several metastases in different localizations, when the tissue is insufficient or has artefacts related for instance to decalcification, when there are problems related to heterogeneity or when biopsy imposes risks [124]. ctDNA can be used to identify resistance to TKIs [126][127][128][129][130][131][132][133][134][135]. Weber et al [136] demonstrated a concordance rate of 90% (179/199) for EGFR mutations between biopsy tissue and ctDNA (plasma) before EGFR TKIs.…”
Section: Doi: 101159/000487440mentioning
confidence: 99%